M2 receptors activation modulates cell growth, migration and differentiation of rat Schwann-like adipose-derived stem cells - Piovesana, Roberta (Cell Death Discov, 2019)
Schwann cells (SCs) play a central role in peripheral nervous system physiology and in the response to axon injury. The ability of SCs to proliferate, secrete growth factors, modulate immune response, migrate and re-myelinate regenerating axons has been largely documented. However, there are several restrictions hindering their clinical application, such as the difficulty in collection and a slow in vitro expansion. Adipose-derived stem cells (ASCs) present good properties for peripheral nerve regenerative medicine. When exposed to specific growth factors in vitro, they can acquire a SC-like phenotype (dASCs) expressing key SCs markers and assuming spindle-shaped morphology. Nevertheless, the differentiated phenotype is unstable and several strategies, including pharmacological stimulation, are being studied to improve differentiation outcomes. Cholinergic receptors are potential pharmacological targets expressed in glial cells. Our previous work demonstrated that muscarinic cholinergic receptors, in particular M2 subtype, are present in SCs and are able to modulate several physiological processes. In the present work, muscarinic receptors expression was characterised and the effects mediated by M2 muscarinic receptor were evaluated in rat dASCs. M2 receptor activation, by the preferred agonist arecaidine propargyl ester (APE), caused a reversible arrest of dASCs cell growth, supported by the downregulation of proteins involved in the maintenance of cell proliferation and upregulation of proteins involved in the differentiation (i.e., c-Jun and Egr-2), without affecting cell survival. Moreover, M2 receptor activation in dASCs enhances a pronounced spindle-shaped morphology, supported by Egr2 upregulation, and inhibits cell migration. Our data clearly demonstrate that rat dASCs express functional muscarinic receptors, in particular M2 subtype, which is able to modulate their physiological and morphological processes, as well as SCs differentiation. These novel findings could open new opportunities for the development of combined cell and pharmacological therapies for peripheral nerve regeneration, harnessing the potential of dASCs and M2 receptors.